Some Recent Developments In The Law Of Banking In Malaysia - Suhanah, Sharifah (Journal of Malaysian and Comparative Law, 2019)
The Central Bank of Malaysia and Banking (Amendment) Act, 1983 introduced a new Section 26A into the Banking Act, 1973. Ever since its introduction into the Banking Act, Section 26A has been the subject of much criticism by bankers and other members of the public alike for its inherent "harshness". It is a small wonder that the section had to be amended so soon after its birth. Thus, on October 10, 1983, the Dewan Rakyat passed the Banking (Amendment) Bill, 1983, whihc sought to amend the Banking Act, 1973 by introducing a new section 24A to discuss the amendment to Section 26A. In this paper, it is sought to discuss the amendment to Section 26A. Before that amendment is discussed, it is pertinent to perhaps that a few words be said about the new arrival into the Banking Act, 1973 - Section 24A.